The Race to the House in the Attractive City: the Access to Housing for Young People in Milan - Costarelli, Igor; Mugnano, Silvia; Terenzi, Alessandra (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2021)
From EXPO 2015 to the COVID-19 pandemic, Milan has been experiencing a period of urban attractiveness and competitiveness on both national and international level. The opportunities generated by a dynamic job market and the high-quality university training have contributed to attract an increasingly large share of young people to the city. However, many youth struggle to access affordable housing in the city as rents are very high and there is a lack of adequate public housing policies to support such demand. This paper investigates the housing pathways of young newcomers to Milan in search for work or study opportunities. Through the analysis of 44 semi-structured interviews with young students and workers between 20 and 35, this paper discusses the lights and shadows of urban attractiveness. While the city has a strong appeal to young people, it is not inclusive for those on low-income. In this context, promoting inclusive housing policies for the younger generations is a necessary condition to guarantee equality of opportunity and social mobility.